2018
DOI: 10.1680/jstbu.16.00175
|View full text |Cite
|
Sign up to set email alerts
|

Tests on composite beams using new connections by adherence

Abstract: Cast in place concrete is often the cheapest solution in the context of conventional construction. However, prefabrication presents advantages in terms of execution time, quality of the structural elements and cost. Thus, the association of precast concrete elements and steel sections in a composite element can result in a high quality structure, executed with greater speed and economy of financial and material resources. Currently, steel to concrete composite connections are not completely adapted to prefabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…(1) As pointed out by Diógenes et al [7], special attention should be given to the fatigue behavior of the connection under vehicular loading and the response under long-term loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) As pointed out by Diógenes et al [7], special attention should be given to the fatigue behavior of the connection under vehicular loading and the response under long-term loading.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 3, this idea comes from the Perfobond shear connectors, in which the shear resistance is expected to be increased considering the confined concrete inside the connector's openings. Flexural tests of composite beams using the improved adhesive connection were also conducted by Diógenes et al [7]. e test results showed that the presence of holes in the connectors had a limited contribution to the flexural stiffness and the loading capacity of the specimens.…”
Section: Introductionmentioning
confidence: 96%
“…The fifth paper (Diógenes et al, 2018) presents and discuss full-scale flexural tests of composite beams using a novel shear connection interfaces based on adhesion, interlocking and friction. Two beams with conventional cast-in-place slabs were also tested for comparison purposes.…”
Section: Structures and Buildingsmentioning
confidence: 99%
“…As shown in Figure 2b, the horizontal shear resistance of the connection is controlled by two interfaces: the grout-concrete interface (interface 1), and the steel-grout interface (interface 2). Papastergiou and Lebet [10] conducted several improvements to this type of connection, including the absence of a bonding layer on the upper flange to improve the brittle behavior of the connection, the presence of circular holes in the steel rib to generate a "dowel effect" [11], and the use of high-performance mortar as the injection [12]. The connection by adhesion, interlocking, and friction offers an alternative solution for the accelerated construction of steel-concrete composite bridges.…”
Section: Introductionmentioning
confidence: 99%